Efficacy thresholds for clinical trials with advanced or metastatic leiomyosarcoma patients: A European Organisation for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group meta-analysis based on a literature review for soft-tissue sarcomas. (September 2021) - Kantidakis, Georgios; Litière, Saskia; Neven, Anouk; Vinches, Marie; Judson, Ian; Schöffski, Patrick; Wardelmann, Eva; Stacchiotti, Silvia; D'Ambrosio, Lorenzo; Marréaud, Sandrine; van der Graaf, Winette T.A.; Kasper, Bernd; et al.
Abstract: Background: In 2002, the European Organisation for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group reported well-established values for conducting phase II trials for soft-tissue sarcomas. An update is provided for leiomyosarcoma (LMS). Materials and methods: Clinical trials with advanced or metastatic LMS were identified via literature review in PubMed (published 2003–2018, ≥10 adult LMS patients). End-points were 3- and 6-month progression-free survival rates (PFSR-3m and PFSR-6m). When estimates could not be derived from publications, data requests were sent out. Treatments were classified as recommended (R-T) or non-recommended (NR-T) according to the ESMO 2018 guidelines. A random effects meta-analysis was used to pool trial-specific estimates for first-line (1L) or pre-treated (2L+) patients separately. The ESMO Magnitude of Clinical Benefit Scale was used to guide the treatment effect to target in future trials. Results: From 47 studies identified, we obtained information on 7 1L and 16 2L+ trials for 1500 LMS patients. Overall, in 1L, PFSR-3m and PFSR-6m were 74% (95% confidence interval [CI] 64–82%) and 58% (95% CI 50–66%), respectively. For 2L+, PFSR-3m was 48% (95% CI 41–54%), and PFSR-6m was 28% (95% CI 22–34%). No difference was observed between R-T and NR-T for first or later lines. Under the alternative that the true benefit amounts to a hazard ratio of 0.65, a PFSR-6m ≥70% can be considered to suggest drug activity in 1L. For 2L+, a PFSR-3m ≥62% or PFSR-6m ≥44% would suggest drug activity. Specific results are also provided for uterine LMS. Conclusions: This work provides a new benchmark for designing phase II studies for advanced or metastatic LMS. Highlights: A novel random effects meta-analysis of 29 clinical trials (2003–2018). More than 1500 patients with advanced/metastatic leiomyosarcoma (LMS). Treatment classification according to the ESMO 2018 guidelines. ESMO Magnitude of Clinical Benefit Scale (MCBS) to target treatment effects. New benchmark for all LMS and specifically for uterine LMS patients.